2013
DOI: 10.3109/09286586.2013.809770
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Risk Indicators of Retinopathy in a Rural Bangladeshi Population with and without Diabetes

Abstract: A high prevalence of retinopathy was observed in this rural Bangladeshi population. In addition to blood glucose control for diabetes, screening for hypertension, obesity, hyperlipidemia and proteinuria as well as adequate treatment of these risk indicators may prevent retinopathy in rural Bangladeshi populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
23
3
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 19 publications
9
23
3
1
Order By: Relevance
“…The results from the local graders are comparable with another study conducted in a small sample in Bangladesh (21.6%) [21], the Hoorn study (23.5%) in Netherlands [22], but higher than the Finnish study in Finland (14.0%) and the Chennai Urban Rural Epidemiology Study (CURES) in India (17.6%)[23]. The prevalence of DR graded by the CERA grader would be higher than 22.1% if the grader had been able to grade 100% of the photos.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The results from the local graders are comparable with another study conducted in a small sample in Bangladesh (21.6%) [21], the Hoorn study (23.5%) in Netherlands [22], but higher than the Finnish study in Finland (14.0%) and the Chennai Urban Rural Epidemiology Study (CURES) in India (17.6%)[23]. The prevalence of DR graded by the CERA grader would be higher than 22.1% if the grader had been able to grade 100% of the photos.…”
Section: Discussionsupporting
confidence: 84%
“…The prevalence of 22.1% was found from 75% of the gradable photos, indicating about 30% would have DR if all photos had been gradable. The higher prevalence of DR in our study compared to the previous study in Bangladesh can be attributed with the fact that our study was conducted in people of age 40 years or older, compared to 25 years and older in another study [21], as DR is consistently associated with older age [21, 22, 24]. …”
Section: Discussioncontrasting
confidence: 58%
“…Similarly, a recent multicenter study of 684 people with diabetes in Colombo, Sri Lanka, reported a prevalence of DR and maculopathy of 18.1% and 9.7%, respectively . Finally, 21.6% of people with diabetes in a rural community in Bangladesh had DR …”
Section: Diabetic Retinopathymentioning
confidence: 99%
“…36 Similarly, a recent multicenter study of 684 people with diabetes in Colombo, Sri Lanka, reported a prevalence of DR and maculopathy of 18.1% and 9.7%, respectively. 57 Finally, 21.6% of people with diabetes in a rural community in Bangladesh had DR. 75 Numerous studies have shown that migrant South Asians have a higher prevalence of DR than Caucasians. In the Diabetic Retinopathy in Various Ethnic groups in UK (DRIVE UK) study, in which 46 962 patients with T2DM from west Yorkshire and southeast London were studied, South Asians had a higher prevalence of DR compared with Caucasians (42.3% vs 38%; OR 1.1).…”
Section: Diabetic Retinopathymentioning
confidence: 99%
“…So far available a population based study of Bangladesh showed that overall prevalence of DR was 5.4% among the rural people of age 30 years or older [22]. Our study demonstrated that compared with the rural people of other areas of Bangladesh, the coastal people had increased prevalence of DR. An estimated global prevalence of 'any DR' was found 6.96% (95CI, 6.87-7.04) [23].…”
Section: Discussionmentioning
confidence: 58%